Genetic diversity and gene flow amongst admixed populations of Ganoderma boninense, causal agent of basal stem rot in African oil palm (Elaeis guineensis Jacq.) in Sarawak (Malaysia), Peninsular Malaysia, and Sumatra (Indonesia). (3rd September 2021) - Wong, W. C.; Tung, H. J.; Fadhilah, M. Nurul; Midot, F.; Lau, S. Y. L.; Melling, L.; Astari, S.; Hadziabdic, Đ.; Trigiano, R. N.; Goh, K. J.; Goh, Y. K.
ABSTRACT: In 1911 and 1917, the first commercial plantings of African oil palm ( Elaeis guineensis Jacq.) were made in Indonesia and Malaysia in Southeast Asia. In less than 15 years, basal stem rot (BSR) was reported in Malaysia. It took nearly another seven decades to identify the main causal agent of BSR as the fungus, Ganoderma boninense . Since then, research efforts have focused on understanding G. boninense disease epidemiology, biology, and etiology, but limited progress was made to characterize pathogen genetic diversity, spatial structure, pathogenicity, and virulence. This study describes pathogen variability, gene flow, population differentiation, and genetic structure of G. boninense in Sarawak (Malaysia), Peninsular Malaysia, and Sumatra (Indonesia) inferred by 16 highly polymorphic cDNA-SSR (simple sequence repeat) markers. Marker-inferred genotypic diversity indicated a high level of pathogen variability among individuals within a population and among different populations. This genetic variability is clearly the result of outcrossing between basidiospores to produce recombinant genotypes. Although our results indicated high gene flow among the populations, there was no significant genetic differentiation among G. boninense populations on a regional scale. It suggested that G. boninense genetic makeup is similar across a wide region. Furthermore, our results revealed the existence of three admixed genetic clusters of G. boninense associated with BSR-diseased oil palms sampled throughout Sarawak, Peninsular Malaysia, and Sumatra. We postulate that the population structure is likely a reflection of the high genetic variability of G. boninense populations. This, in turn, could be explained by highly successful outcrossing between basidiospores of G. boninense from Southeast Asia and introduced genetic sources from various regions of the world, as well as regional adaptation of various pathogen genotypes to different palm hosts. Pathogen variability and population structure could be employed to deduce the epidemiology of G. boninense, as well as the implications of plantation cultural practices on BSR disease control in different regions.